2017
DOI: 10.1111/1365-2435.12884
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasion modifies the co‐occurrence patterns of insects along a stress gradient

Abstract: Summary Biological invasions have become one of the most important drivers of biodiversity loss and ecosystem change world‐wide. However, it is still unclear how invasions may interact with local abiotic stressors, which are expected to increase as global change intensifies. Furthermore, we know little about the response to biological invasions of insects, despite their disproportionate contribution to global animal biodiversity. The aim of the present work is to investigate the impact of an invasive aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 60 publications
0
42
0
4
Order By: Relevance
“…At high abiotic stress in intertidal horizontal habitats, however, the trophic niche of O. edulis became more δ 15 N enriched in the presence of M. gigas , which may indicate an increase in trophic level, while M. gigas' trophic niche remained stable. Contrary to the theory that niche partitioning facilitates coexistence of competitors at higher abiotic stress levels (Bulleri et al, ; Carbonell et al, ), changes in trophic niches in this context were not indicative of trophic re‐organization nor of individual niche specialization (Britton et al, ; Costa‐Pereira & Rudolf, ). Therefore, it is unlikely that exploitative competition was a driving factor in intertidal habitats.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…At high abiotic stress in intertidal horizontal habitats, however, the trophic niche of O. edulis became more δ 15 N enriched in the presence of M. gigas , which may indicate an increase in trophic level, while M. gigas' trophic niche remained stable. Contrary to the theory that niche partitioning facilitates coexistence of competitors at higher abiotic stress levels (Bulleri et al, ; Carbonell et al, ), changes in trophic niches in this context were not indicative of trophic re‐organization nor of individual niche specialization (Britton et al, ; Costa‐Pereira & Rudolf, ). Therefore, it is unlikely that exploitative competition was a driving factor in intertidal habitats.…”
Section: Discussionmentioning
confidence: 56%
“…Here, we have shown that, in the presence of a morphologically similar competitor, invasion success was determined by abiotic stress, and that surface topography drives differences in biotic interaction type. Specifically, this study has shown that niche partitioning and facilitation were primarily driven by surface topography rather than abiotic stress (Bruno et al, 2003;Carbonell et al, 2017) and suggests that differences in ecological niches, such as those created by orientation of substratum is an under-rated factor in species interactions and should be included in future studies aiming to clarify the role of invasive competitors.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations